Brief Report: Articular Ankle Fracture Results in Increased Synovitis, Synovial Macrophage Infiltration, and Synovial Fluid Concentrations of Inflammatory Cytokines and Chemokines. Issue 5 (May 2015) - Furman, Bridgette D.; Kimmerling, Kelly A.; Zura, Robert D.; Reilly, Rachel M.; Zlowodzki, Michal P.; Huebner, Janet L.; Kraus, Virginia B.; Guilak, Farshid; Olson, Steven A.
<x xml:space="preserve">Abstract</x> Objective The inflammatory response following an articular fracture is thought to play a role in the development of posttraumatic arthritis (PTA) but has not been well characterized. The objective of this study was to characterize the acute inflammatory response, both locally and systemically, in joint synovium, synovial fluid (SF), and serum following articular fracture of the ankle. We hypothesized that intraarticular fracture would alter the synovial environment and lead to increased local and systemic inflammation. Methods Synovial tissue biopsy specimens, SF samples, and serum samples were collected from patients with an acute articular ankle fracture (n = 6). Additional samples (normal, ankle osteoarthritis [OA], and knee OA [n = 6 per group]) were included for comparative analyses. Synovial tissue was assessed for synovitis and macrophage count. SF and serum were assessed for cytokines (interferon‐γ [IFNγ], interleukin‐1β [IL‐1β], IL‐6, IL‐8, IL‐10, IL‐12p70, and tumor necrosis factor α) and chemokines (eotaxin, eotaxin 3, IFNγ‐inducible 10‐kd protein, monocyte chemotactic protein 1 [MCP‐1], MCP‐4, macrophage‐derived chemokine, macrophage inflammatory protein 1β, and thymus and activation–regulated chemokine). Results Synovitis scores were significantly higher in ankle fracture tissue compared with normal ankle tissue (P = 0.007), and there was a trend toward an increased abundance of CD68+ macrophages in ankle fracture synovium compared with normal knee synovium (P = 0.06). The concentrations of all cytokines and chemokines were elevated in the SF of patients with ankle fracture compared with those in SF from OA patients with no history of trauma. Only the concentration of IL‐6 was significantly increased in the serum of patients with ankle fracture compared with normal serum (P = 0.027). Conclusion Articular fracture of the ankle increased acute local inflammation, as indicated by increased synovitis, increased macrophage infiltration into synovial tissue, and increased SF concentrations of biomarkers of inflammation. Characterizing the acute response to articular fracture provides insight into the healing process and may help to identify patients who may be at greater risk of PTA.